Response of Renal Podocytes to Excessive Hydrostatic Pressure: a Pathophysiologic Cascade in a Malignant Hypertension Model - Ramzia Abu Hamad; Sylvia Berman; Yafit Hachmo; Moshe Stark; Fadia Hasan; Keren Doenyas-Barak; Shai Efrati (Karger Publishers, 2017)
Background/Aims: Renal injuries induced by increased intra-glomerular pressure coincide with podocyte detachment from the glomerular basement membrane (GBM). In previous studies, it was demonstrated that mesangial cells have a crucial role in the pathogenesis of malignant hypertension. However, the exact pathophysiological cascade responsible for podocyte detachment and its relationship with mesangial cells has not been fully elucidated yet and this was the aim of the current study. Methods: Rat renal mesangial or podocytes were exposed to high hydrostatic pressure in an in-vitro model of malignant hypertension. The resulted effects on podocyte detachment, apoptosis and expression of podocin and integrinβ1 in addition to Angiotensin-II and TGF-β1 generation were evaluated. To simulate the paracrine effect podocytes were placed in mesangial cell media pre-exposed to pressure, or in media enriched with Angiotensin-II, TGF-β1 or receptor blockers. Results: High pressure resulted in increased Angiotensin-II levels in mesangial and podocyte cells. Angiotensin-II via the AT1 receptors reduced podocin expression and integrinβ1, culminating in detachment of both viable and apoptotic podocytes. Mesangial cells exposed to pressure had a greater increase in Angiotensin-II than pressure-exposed podocytes. The massively increased concentration of Angiotensin-II by mesangial cells, together with increased TGF-β1 production, resulted in increased apoptosis and detachment of non-viable apoptotic podocytes. Unlike the direct effect of pressure on podocytes, the mesangial mediated effects were not related to changes in adhesion proteins expression. Conclusions: Hypertension induces podocyte detachment by autocrine and paracrine effects. In a direct response to pressure, podocytes increase Angiotensin-II levels. This leads, via AT1 receptors, to structural changes in adhesion proteins, culminating in viable podocyte detachment. Paracrine effects of hypertension, mediated by mesangial cells, lead to higher levels of both Angiotensin-II and TGF-β1, culminating in apoptosis and detachment of non-viable podocytes.